(untitled) (Research, Society and Development, 2022)
The LGBTQIA+ population is marginalized in contemporary society. The obstacles to which they are exposed promote vulnerabilities and social negligence, including those related to access in the context of health care. Besides, professional mistakes are common during consultations with LGBTQIA+ people and, therefore, they should be argued in the field of medical education. This manuscript aims to discusses the medical education and health practices addressed to these people. Narrative review, through scientific platforms, and qualitative analysis. Sixteen texts related to the theme were used. The invisibility of data that could guide best professional practices and strengthen public policies applied to the group stands out. It is observed that the LGBTQIA+ population is commonly marginalized in health care, due to inadequate professional practices. As a cause, medical training is noteworthy, both for the curricula that involve medical schools and for teaching practices that disregard the subject. Ensuring adequate health care may promote improvements in the experiences lived by the LGBTQIA+ population, given their health demands and confrontations in their daily lives. Health support should consider specific demands, especially related to health promotion. Medical education must be modified in order to ensure that professionals work properly with the LGBTQIA+ population. The lack of consistent data on the population under discussion jeopardizes public policies and health practices. Moreover, the topic receives little attention in medical education courses, a fact that indicates the need for changes in the curricula as well as in didactic actions of professors.